Ensuring competitiveness in the XXI century: use of management tools in the internet-economy (on the example of banks) - A. A. Madyarov (Вестник университета)
The formation of the Internet economy places special demands on the development of a system of organisational influences used to solve problems of adaptation to changes in the external environment and internal integration. At the same time, the effectiveness of the updated combination of management tools should be sufficient to ensure competitiveness during the implementation of the strategic process. The relevance of studying and systematising the practices used by the subjects of the digital economy is justified by the transformational processes of the information society, representing both scientific and practical interest. Consideration of the works of leading Russian and foreign scientists specialising in the development of the Internet economy through the use of the management tools as well as the results of the People’s rating of customer service by domestic banks allows us to draw conclusions about the need to introduce special approaches to respond to the challenges the threats of the latest strategic context. In addition, they should be combined considering the results of the analysis and systematisation of this study. The article concludes with brief findings on the results of the research, emphasising the importance of continuing to study examples of ensuring the competitiveness by Russian companies in the XXI century: identifying industry features may be of interest for replicating best practices in the Internet economy.